2018
DOI: 10.1038/s41467-018-05258-6
|View full text |Cite
|
Sign up to set email alerts
|

FoxM1 repression during human aging leads to mitotic decline and aneuploidy-driven full senescence

Abstract: Aneuploidy, an abnormal chromosome number, has been linked to aging and age-associated diseases, but the underlying molecular mechanisms remain unknown. Here we show, through direct live-cell imaging of young, middle-aged, and old-aged primary human dermal fibroblasts, that aneuploidy increases with aging due to general dysfunction of the mitotic machinery. Increased chromosome mis-segregation in elderly mitotic cells correlates with an early senescence-associated secretory phenotype (SASP) and repression of F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
97
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(122 citation statements)
references
References 70 publications
11
97
0
Order By: Relevance
“…The regenerating tail is an oxidative environment and we show here that foxm1 expression requires ROS. Furthermore, Foxm1 has been shown to ensure chromosomal stability and genome integrity in U2OS and aged fibroblasts [25,26], raising the intriguing possibility that Foxm1 might ensure that the expansion of the progenitor pool does not lead to genetic instability during regeneration.…”
Section: Foxm1 Regulates the Fate Of Dividing Progenitors During Regementioning
confidence: 99%
See 1 more Smart Citation
“…The regenerating tail is an oxidative environment and we show here that foxm1 expression requires ROS. Furthermore, Foxm1 has been shown to ensure chromosomal stability and genome integrity in U2OS and aged fibroblasts [25,26], raising the intriguing possibility that Foxm1 might ensure that the expansion of the progenitor pool does not lead to genetic instability during regeneration.…”
Section: Foxm1 Regulates the Fate Of Dividing Progenitors During Regementioning
confidence: 99%
“…The regenerating tail is an oxidative environment and we show here that foxm1 expression requires ROS. Furthermore, Foxm1 has been shown to ensure chromosomal stability and genome integrity in U2OS and aged fibroblasts [25,26], raising the intriguing possibility that Foxm1 might ensure that the expansion of the progenitor pool does not lead to genetic instability during regeneration.The expansion of the neural stem cell pool is required for spinal cord regeneration in axolotl, zebrafish and Xenopus [4,8,27]. Here we show that regeneration also requires the precise control of neuronal differentiation.…”
mentioning
confidence: 99%
“…FOXM1 also plays an important role in mitotic maintenance, and we observed enriched mitotic expression with FOXM1 depletion. In recent studies, decreased levels of FOXM1 was shown to cause mitotic decline, genomic instability, and senescence during human aging (Macedo et al, 2018). Conversely, FOXM1 overexpression was found to promote mitotic defects and genomic instability (Pfister et al, 2018).…”
Section: Hgsc Tissues and Cells Show Robust Overexpression Of Both Fomentioning
confidence: 99%
“…Additionally, we found reduced expression of the transcription factor FoxM1 in severely aneuploid cells, whose repression has been recently shown to lead to senescence during aging (225). The polycomb group (PcG) histone H3 lysin-27 methyltransferase EZH2, another down-regulated candidate gene in aneuploidy-induced senescent cells, has been reported to be suppressed in senescent cells and its down-regulation promotes senescence (227).…”
Section: Mild Chromosome Mis-segregation Can Be Tolerated and Propagamentioning
confidence: 70%
“…25A and 25B), leading to our hypothesis that downregulation of FoxM1 might play a role in senescence induction. Interestingly, a recent report studying aneuploidy in the aging context showed FoxM1 repression in aged primary human fibroblasts which exhibited increased chromosome mis-segregation and aneuploidy (225). Importantly, they found that depletion of FoxM1 in young fibroblasts increased mitotic defects and induced senescence, and restoration of FoxM1 in elderly fibroblasts prevented aneuploidy and delayed the onset of senescence, leading to their conclusion that FoxM1 levels regulate aneuploidy and senescence.…”
Section: Activation Of Nf-κb and P38mapk And Potential Candidate Genementioning
confidence: 97%